2021
DOI: 10.1016/j.rmed.2021.106550
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the HACOR score in predicting success of CPAP in COVID-19-related hypoxemia

Abstract: Introduction In COVID-19 associated hypoxemic acute respiratory failure (ARF) without mandatory indication for urgent endotracheal intubation, a trial of CPAP may be considered. We aimed to evaluate HACOR (heart rate, acidosis, consciousness, oxygenation, respiratory rate) score performance in these patients as predictor of CPAP failure. Methods Prospective observational multicentric study (three centers in different countries), including adult patients with SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
1
29
1
2
Order By: Relevance
“…The HACOR score was not able to predict COT failure. Guia et al observed a significant correlation of HACOR scores > 5 with CPAP failure in COVID-19 patients with ARF [18]. In their study cohort, however, patients seemed to be in more severe clinical conditions, with higher RRs and significantly lower P/F ratios compared to the cohort of patients we evaluated.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The HACOR score was not able to predict COT failure. Guia et al observed a significant correlation of HACOR scores > 5 with CPAP failure in COVID-19 patients with ARF [18]. In their study cohort, however, patients seemed to be in more severe clinical conditions, with higher RRs and significantly lower P/F ratios compared to the cohort of patients we evaluated.…”
Section: Discussioncontrasting
confidence: 52%
“…The ROX (Respiratory rate -OXygenation) index, proposed by Roca et al [15] for the prediction of HFNC failure in patients with pneumonia and ARF, was shown to correlate with the need for hospital admission, mechanical ventilation, and mortality risk in COVID-19 patients [16]. The HACOR score (Heart rate, Acidosis, Consciousness level, Oxygenation and Respiratory rate), proposed by Duan et al [17] for the prediction of NIV failure in hypoxemia due to several causes, was evaluated for the prediction of CPAP failure in COVID-19 patients with ARF [18] and was found to be comparable in its predictive power to the partial arterial oxygen pressure/inspired oxygen fraction (PaO 2 /FiO 2 or P/F) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several attempts to investigate predictors of failure of NIV and/or HFNO in patients with COVID-19 pneumonia such as HACOR score [14] and ROX index [15]. More recently a machine learning algorithm based on vital signs, laboratory values, and demographic data outperformed the ROX index in predicting the need for intubation in COVID-19 patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been explored as a predictive score for CPAP failure in a multicenter study. Although the performance was quite good (82%), it was similar to PaO 2 /FiO 2 ratio (81.25%) ( 84 ).…”
Section: Evaluation Of the Response To Srnimentioning
confidence: 90%